Efficiency of storage heaters in private housing estates of Ukraine - Клён, Андрей Николаевич (Technology audit and production reserves, 2015)
This paper focuses on the economic efficiency issues of heating systems employment based on storage heaters. There have been calculated capitalized and current charges involved in establishing and employment of heating systems based on storage heaters. There have been determined payback period upon their employment. As a result of the research conducted by the author, he has reached a conclusion that employment of heating systems based on storage heaters appears profitable not only as compared to electric heating convectors but even as compared to the gas heating. There has been determined that employment of such systems is cost effective. Despite comparatively high initial expenses, heating systems based on storage heaters pay off in 3-8 years compared to the gas heating and in 7-13,5 years compared to electric heating convectors. It is worth mentioning that the main deterrent restraining the economic planning and calculations of technical-and-economic indexes for different heating systems is uncertainty of fee policy in the field of housing and utilities services, coming from unstable economic situation in the country and also political speculations in this area.